Measurement of f1(1285) production in pp collisions at √s = 13 TeV - Trubnikov, Vyacheslav; The ALICE collaboration (Physics Letters B, 2025)
This study presents the first measurement of the f_1(1285) resonance using the ALICE detector in inelastic proton–proton collisions at a center-of-mass energy of √s = 13 TeV. The resonance is reconstructed at midrapidity (|y| < 0.5) through the hadronic decay channel f_1(1285) -> K_S^0 K^± π^∓. Key measurements include the determination of its mass, transverse-momentum integrated yield, and average transverse momentum. Additionally, the ratio of the transverse-momentum integrated yield of f_1(1285) to pion is compared with calculations from the canonical statistical hadronization model. The model calculation, assuming a zero total strangeness content for f_1(1285), reproduces the data within 1σ deviation, shedding light on the quark composition of f_1(1285).